Understanding Women's Aspirations: A Study in Three Indian States. Issue 1 (June 2019) - Chaturvedi, Gitanjali; Sahai, Garima
This study provides an insight to the aspirations of women and girls in three states in India. This study is a product of primary research, based on focus group discussions and interviews, that highlights the voices of women in remote rural districts as well as tribal areas where women want jobs, security, savings, education and a happy life. Women in peri-urban areas are more confident of realizing their aspirations than those in rural areas. Younger women are more aspirational, and thus they are less willing to do manual labour. They aspire for white-collar jobs with the government and the security that the jobs provide. As girls get more educated, it is important to match their skills with the labour market, ensure safe and reliable transport and public spaces so that they can achieve their aspirations. Big hurdles to achieving their dreams are the mindsets at home—notably that of parents, husbands and in-laws—that continue to determine how far they will be educated and whether they will have jobs and careers.